Teaching the Secrets of Folk Crafts Using Innovative Technologies (On the Example of Act and Smart Technology) (Journal of Pedagogical Inventions and Practices, 2022)
This article describes the use of innovative technologies in technology classes for students, the use of SMART technology in teaching folk crafts